COVID-19 and New Forms of Acute Pneumonia. It's Time for A Brainstorming Session - Klepikov Igor (International Journal of Coronaviruses, 2020)
This perspective calls for cross‑disciplinary brainstorming on novel COVID‑19 pneumonia phenotypes. It discusses hypotheses on immune dysregulation, microvascular injury, and tailored respiratory strategies.
Keywords: Covid-19